Pseudo-diffusion effects in lung MRI - Ziener, Christian H.; Kurz, Felix T.; Schlemmer, Heinz-Peter; Buschle, Lukas R. (Journal of magnetic resonance, 2019)
Magnetic resonance imaging of lung tissue is strongly influenced by susceptibility effects between spin-bearing water molecules and air-filled alveoli. The measured lineshape, however, also depends on the interplay between susceptibility effects and blood-flow around alveoli that can be approximated as pseudo-diffusion. Both effects are quantitatively described by the Bloch-Torrey-equation, which was so far only solved for dephasing on the alveolar surface. In this work, we extend this model to the whole range of physiological relevant air volume fractions. The results agree very well with in vivo measurements in human lung tissue.
Available online 29 November 2018
Gesehen am 11.07.2019